2019
DOI: 10.2298/ciceq180828014k
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound - assisted extraction of phenolic compounds from wood apple pulp: Identification of phytochemicals using GC-MS

Abstract: Article Highlights• Response surface methodology was applied for optimization of solvent extraction and ultrasound-assisted extraction • UAE is an effective method to obtain maximum yield with minimum time and solvent consumption • GC-MS analysis was carried out to identify the bioactive compounds present in the extract obtained from various extraction techniques AbstractIn the present work, ultrasound-assisted extraction (UAE) was employed to extract the phenolic compounds from wood apple pulp. A Box-Behnken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The Folin-Ciocalteu (FC) method was utilized in a study to measure the total phenolic content (TPC) of wood apple pulp. The findings revealed that the phenolic content yield varied from 3.73 to 11.34 mg GAE/g [ 29 ]. In another study, the TPC was found high in the pulp (35.72 μg GAE/mg) of wood apple extracts [ 1 ].…”
Section: Phytochemical Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The Folin-Ciocalteu (FC) method was utilized in a study to measure the total phenolic content (TPC) of wood apple pulp. The findings revealed that the phenolic content yield varied from 3.73 to 11.34 mg GAE/g [ 29 ]. In another study, the TPC was found high in the pulp (35.72 μg GAE/mg) of wood apple extracts [ 1 ].…”
Section: Phytochemical Profilementioning
confidence: 99%
“…A study was conducted in which the total flavonoid content (TFC) was determined in wood apple pulp using the aluminum chloride method. Results showed that flavonoid content range from 1.59 to 4.39 mg RE/g [ 29 ]. In a different study, a wide range of biological actions exhibited by flavonoids includes the prevention of cell proliferation, activation of apoptosis, inhibition of enzymes, as well as additional antibacterial and antioxidant properties.…”
Section: Phytochemical Profilementioning
confidence: 99%
“…Its environmentally friendly profile, coupled with minimal physical and chemical hazards, reinforces its standing as a preferred extraction technique. [22][23][24][25][26] UAE focuses on optimizing processing parameters to maximize bioactive yield. Extracts obtained through UAE under optimal conditions contain the highest phenolic concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This innovative approach employs sound waves to improve solvent penetration into plant cells, significantly enhancing superior selectivity, productivity, low solvent consumption, cost‐effectiveness, ease of operation, and a shortened extraction time. Its environmentally friendly profile, coupled with minimal physical and chemical hazards, reinforces its standing as a preferred extraction technique [22–26] . UAE focuses on optimizing processing parameters to maximize bioactive yield.…”
Section: Introductionmentioning
confidence: 99%